The Urgency of the Asset Confiscation Law in on Effort to Restore State Losses Due to Corruption - Mela Agustina; Nurfadilah Dwinanda Pertiwi; Angelica Angelica; Waluyadi Waluyadi; Ari Nurhaqi (Riviera Publishing, 2025)
Corruption in Indonesia continues to cause significant state financial losses and erode public trust in governance. Traditional criminal sanctions such as imprisonment and fines have proven insufficient to deter corrupt actors, particularly due to the absence of a clear legal framework allowing asset confiscation without requiring a criminal conviction. This study examines the urgency of ratifying the Asset Forfeiture Law as a strategic tool to recover state losses resulting from corruption crimes. Employing a normative juridical approach, the study analyzes relevant laws, literature, and documentation using qualitative and prescriptive methods. Findings reveal that the Asset Forfeiture Law, through its in rem-based asset confiscation mechanism, addresses critical gaps by enabling the state to seize assets suspected of being derived from criminal acts regardless of the perpetrator’s criminal conviction. This progressive legal reform not only enhances law enforcement effectiveness but also reinforces social justice by preventing corrupt individuals from benefiting from illicit gains. The study underscores the need for coherent, comprehensive regulations aligned with international standards, facilitating more efficient asset recovery and strengthening public confidence in the legal system. The implications highlight the Asset Forfeiture Law’s role in advancing Indonesia’s anti- corruption framework and promoting good governance.